The Alcohol Hangover Causes, Consequences, and Treatment - Verster, Joris; Arnoldy, Lizanne; Benson, Sarah; Scholey, Andrew; Stock, Ann-Kathrin (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The seeds and fruits (or their parts) of Iberoamerican crops have high nutritional and functional properties which could be utilized in a wide range of foods. The crops included in this book are amaranth (Amaranthus spp.), quinoa (Chenopodium quinoa), kañiwa (Chenopodium pallidicaule), chia (Salvia hispanica L.), Andean maize (Zea mays L.), moringa (Moringa oleifera), yvapuru (Plinia peruviana), kurugua (Sicana odorifera), sacha inchi (Plukenetia huayllabambana), camu camu (Myrciaria dubia), mango (Mangifera indica), tarwi (Lupinus mutabilis), peanut (Arachis hypogaea L.) and taro (Colocasia esculenta), all of them still underutilized. Their cultivation is low; nevertheless, in recent years, the worldwide demand for some of them has increased immensely, resulting in an increase in their production. The ancient Iberoamerican crops have been widely recognized for their nutritional value by food scientists and food producers because they contain high-quality proteins and large quantities of micronutrients such as minerals, vitamins and bioactive compounds. In addition, they are gluten-free, which makes them suitable for people suffering from various gluten intolerances. This book summarizes the large amount of investigations in this field in the last year and provides knowledge within all the relevant areas of food science. The editors hope that this book will contribute to an increased use of these products in human nutrition by consumers worldwide.